'Imagined futures' in the navigation and management of uncertainty for young women in Aotearoa, New Zealand. (December 2019) - France, Alan; Pukepuke, Tepora; Cowie, Lucy; Mayeda, David; Chetty, Marilyn
Uncertainty and insecurity in the labour market for young women have increased dramatically. Globally, notions of 'precariousness', 'flexibility' and 'gig working' have grown and the idea of secure permanent work and 'career building' is seen as a thing of the past. Simultaneously, and not unconnected, we have also seen the 'massification' of higher education where more young women than ever are entering university aiming to improve their situation in the labour market. But how, in these uncertain times, are they imagining their futures? What is influencing their planning and what are their motivations? These questions were explored with a diverse group of young women (n = 26) who were third-year students at a university in Aotearoa New Zealand. The analysis of their interviews draws on the work of Pierre Bourdieu and findings highlight the need to recognise the important relationships between their past, the present and their imagined futures.